Prevalence of hyperglycaemia, prediabetes and type-2 diabetes mellitus in the adult Lebanese population: results of the PREDICT study - Charles Saab; Mounzer Saleh; Joelle Obeid; Hala Saghir; Rana Abdel-Samad; Jessica Saliba; Paola Atallah (BMC Public Health)
Abstract Background The literature on the prevalence of glycaemia dysregulation among Lebanese adults is inconclusive. Methods The PREDICT study was a national cross-sectional study that aimed to report the prevalence of incidental hyperglycaemia, prediabetes or type-2 diabetes mellitus (DM) in Lebanese adults. Glycaemia was measured by blood glucose finger prick test and data on demographic, medical history and lifestyle were collected. Results Out of 10,448 subjects included in the analysis, 2785 belonged to the prediabetes group (Group P), with 93 subjects (0.9%) reporting a prior diagnosis of prediabetes and 2692 (25.8%) with study-determined glycaemia in the prediabetes range. Additionally, 1135 subjects (10.9%) reported a prior diagnosis of type-2 DM and 640 (6.1%) had study-determined glycaemia in the type-2 DM range, making up 1775 subjects in the type-2 DM group (Group D). Hyperglycaemia significantly increased with age, and was detected in elderly (58.5%), older adults (46.3%) and younger adults (33.0%), p < 0.0001. Subjects with normal glycaemia were 43.7 ± 15.2 years old; while age in group P was 46.4 ± 15.6 years and in group D it was 57.6 ± 14.6 years (p < 0.001). Group P subjects had a body mass index (BMI) of 26.7 ± 4.6 kg/m2 and Group D subjects had a BMI of 27.9 ± 5.1 kg/m2, significantly higher than BMI in the normal glycaemia group (26.2 ± 4.4 kg/m2, p < 0.001). Among subjects in Group P (n = 2785) or in Group D (n = 1775), respectively 1648 (59.2%) and 297 (16.7%) had reported no known risk factors for glycaemia disorders, equivalent to 15.8% and 2.8% of study population. Conclusions In this study, 10% of subjects had a prior diagnosis of type-2 DM. Alarmingly, 6% and 26% of subjects had incidentally-detected hyperglycaemia in the type-2 DM and prediabetes range, respectively. The prevalence of hyperglycaemia and of prediabetes that might progress to type-2 DM poses a serious threat to the Lebanese population and healthcare system; especially among younger and seemingly healthy adults. Hence, this study shed the light on potentially undiagnosed cases of glycaemia disorders, urging the need for early detection and timely management to curb the medical, social and health burden of type-2 DM.